Cultural Legal Studies : Law's Popular Cultures and the Metamorphosis of Law. - Sharp, Cassandra (Taylor and Francis, 2015)
"What can popular cultures offer law, as a basis for critical practice? This introduction to the 'cultural legal studies' movement takes up this question as it presents a new encounter with the 'cultural turn' in law and legal theory. Moving beyond the 'law ands' (literature, humanities, culture, film) on which it is based, cultural legal studies aims to metamorphose law and the legalities that underpin its popular imaginary. To this end, the collection brings together leading scholars from Australia, Canada, the United Kingdom, and the United States. Presenting a long-overdue identification and framing of its scope, methodologies and practice, and drawing on three different modes of cultural legal studies - storytelling, technology and jurisprudence - the collection showcases the intersectional practices of cultural legal studies and law in its popular cultural mode. In this respect, contributors to the collection deploy differentiated modes of cultural legal studies practice, adopting diverse philosophical, disciplinary, methodological and theoretical approaches and subjects of examination. The collection draws on this mix of diversity and homogeneity to argue that we must take seriously an interrogation of law as culture- that is, not asking how a text 'represents'law, but how the representational nature of both law and culture intersect: in short, how the 'juridical' becomes visible in various cultural forms and their technological manifestations, and so how law's popular cultures actively metamorphose law."--